2016
DOI: 10.1155/2016/1473578
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of miRNA-122 Induced by Liver Toxicants in Zebrafish

Abstract: MicroRNA-122 (miRNA-122), also known as liver-specific miRNA, has recently been shown to be a potent biomarker in response to liver injury in mammals. The objective of this study was to examine its expression in response to toxicant treatment and acute liver damage, using the zebrafish system as an alternative model organism. For the hepatotoxicity assay, larval zebrafish were arrayed in 24-well plates. Adult zebrafish were also tested and arrayed in 200 mL cages. Animals were exposed to liver toxicants (tamox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In past studies on rats [51,52], the miR-122 levels in healthy liver tissue increased, while toxic substances and diseases increase miR-122 expression in the serum. In zebrafish [53], the toxic liver damage induced by tamoxifen or APAP increased the expression of hepatic specific miR-122 in liver tissue. In dogs with liver disease, the expression of miR-122 in serum was significantly higher than that in healthy dogs [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In past studies on rats [51,52], the miR-122 levels in healthy liver tissue increased, while toxic substances and diseases increase miR-122 expression in the serum. In zebrafish [53], the toxic liver damage induced by tamoxifen or APAP increased the expression of hepatic specific miR-122 in liver tissue. In dogs with liver disease, the expression of miR-122 in serum was significantly higher than that in healthy dogs [54].…”
Section: Discussionmentioning
confidence: 99%
“…This molecule plays a key role in liver physiology, where it participates in hepatocyte differentiation, supports spontaneous regeneration, and takes part in liver homeostasis, lipid metabolism, and cholesterol synthesis [33]. In addition, many studies have shown the sensitivity and specificity of miR-122 as a circulating biomarker of liver injury in animals, such as chimpanzees [50], mice [30], rats [51,52], zebrafish [53], and dogs [54]. The literature also reported the potential use of miR-122 in humans as a biomarker for liver diseases caused, among others, by drug-induced liver injury (DILI) [29,55], hepatitis B and C [25,56], and ethanol consumption [57].…”
Section: Discussionmentioning
confidence: 99%
“…miR‐122 is highly expressed in hepatocytes accounting for up to 70% of the total liver miRNA content . Multiple studies have demonstrated the sensitivity and specificity of miR‐122 as a circulating biomarker of liver injury in chimpanzees, mice, rats, zebrafish, and in human studies of different liver diseases including drug‐induced liver injury (DILI), hepatitis C, and ethanol consumption . miR‐122 has received regulatory support for further qualification by the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA) in the context of DILI .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they concluded that in adult zebrafish, the same hepatotoxicant specifically alters the expression of genes encoding albumin-like protein, ceruloplasmin, liver fatty acid binding protein (L-Fabp10a), and transferrin, all of them regarded as biomarkers of hepatotoxicity 75 . In addition, liver expression of miR-122, a liver-specific toxicity biomarker in mammals, was also reported to be a possible biomarker of hepatotoxicity in zebrafish 76 .…”
Section: Examples Of Applicationsmentioning
confidence: 99%